1997
DOI: 10.1038/sj.leu.2400548
|View full text |Cite
|
Sign up to set email alerts
|

A fraction unresponsive to growth inhibition by TGF-β among the high-proliferative potential progenitor cells in bone marrow of p53-deficient mice

Abstract: Transforming growth factor-␤ (TGF-␤) has been found to block GM), erythroid progenitors (BFU-E), megakaryocyte progeni- mice and were mated to produce homozygous p53-deficient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…This and the demonstration that overexpression of mutant p53 can confer partial resistance to TGF-␤1 have suggested that p53 may be involved in TGF-␤1 growth-inhibitory pathways (48,49). A role for p53 in the growth-inhibitory actions of TGF-␤1 on primitive hematopoietic cells was also recently suggested following the detection of a TGF-␤1-resistant subpopulation in HPP-CFC (very primitive progenitors) isolated from p53-deficient but not wild type mice (50). In contrast to the data obtained from Sasaki et al Recent studies on leukemic cell lines have suggested that the proapoptotic effects of TGF-␤1 may be mediated in part through the modulation of Bcl-2 family members (37)(38)(39).…”
Section: Tgf-␤1-mediated Apoptosis Is Inhibited By Expression Of Bcl-mentioning
confidence: 99%
See 1 more Smart Citation
“…This and the demonstration that overexpression of mutant p53 can confer partial resistance to TGF-␤1 have suggested that p53 may be involved in TGF-␤1 growth-inhibitory pathways (48,49). A role for p53 in the growth-inhibitory actions of TGF-␤1 on primitive hematopoietic cells was also recently suggested following the detection of a TGF-␤1-resistant subpopulation in HPP-CFC (very primitive progenitors) isolated from p53-deficient but not wild type mice (50). In contrast to the data obtained from Sasaki et al Recent studies on leukemic cell lines have suggested that the proapoptotic effects of TGF-␤1 may be mediated in part through the modulation of Bcl-2 family members (37)(38)(39).…”
Section: Tgf-␤1-mediated Apoptosis Is Inhibited By Expression Of Bcl-mentioning
confidence: 99%
“…Studies on nonhematopoietic cells have implicated the tumor suppressor p53 in the growth-suppressive effects of TGF-␤1 (46 -49). The detection of a TGF-␤1-resistant subpopulation in high proliferative potential colony-forming cells (HPP-CFC) isolated from p53-deficient mice (but not wild type littermates) has suggested that p53 may play a role in TGF-␤1 growth-inhibitory pathways in hematopoietic cells (50). In order to test this, we utilized a multipotent and IL-3-dependent FDCP-Mix cell line isolated from long term bone marrow cultures derived from p53 null mice (p53 null FDCP-Mix).…”
Section: Tgf-␤1 Inhibits the Growth Of Fdcp-mix Cells-mentioning
confidence: 99%
“…The HPP-CFC were assayed by a method previously described, with slight modifications. 18,19 Marrow cells from 5-FU-treated mice were suspended at a density of 10 5 cells/mL in IMDM medium containing 0.3% purified agar and 20% fetal bovine serum (FBS), with various combinations of cytokines, and plated into Petri dishes (1.5 mL/dish). Cultures were incubated at 37°C, 5% CO 2 and 5%O 2 for 14 days.…”
Section: Assay Methods For High Proliferative Potential Colony Formingmentioning
confidence: 99%
“…Moreover, we should note that primitive hematopoietic stem cells, but not more mature progenitor cells, express the growth-inhibitory signalling molecule, the tumour growth factor (TGF) beta receptor [49,50]. TGF-beta does not increase the number of colonies generated in culture from WT stem/progenitor cells.…”
Section: Radiation Effects On Hematopoietic Stem/progenitor Cellsmentioning
confidence: 99%
“…TGF-beta does not increase the number of colonies generated in culture from WT stem/progenitor cells. Interestingly, such negative regulation of TGF-beta for primitive stem/progenitor cells fails when bone marrow cells are harvested from p53 KO [50]. It is also of interest that mice overexpressing the SV40-large T gene and made p53-deficient can suffer from a myelodysplastic syndrome, in which lack of regulation of growing potential in the primitive stem/progenitor cells is presumably induced by dysfunction of the negative regulator TGFbeta [51].…”
Section: Radiation Effects On Hematopoietic Stem/progenitor Cellsmentioning
confidence: 99%